Sistem Agribisnis Sayur Hidroponik Di Kabupaten Sambas - Sari, Dian; Wilujeng, Wilis Widi; Novita, Uray Dian; Mulyati, Sri (CV.ITTC INDONESIA, 2024)
This research aims to determine the agribusiness system from upstream to downstream and supporting institutions for hydroponic vegetable farmers in Sambas Regency. The research method used is descriptive quantitative using an agribusiness system approach based on each subsystem, including input subsystem, agricultural subsystem, marketing subsystem and supporting subsystem. This research was carried out in Sambas Regency considering that hydroponic vegetables are widely grown in this area. The sample was determined intentionally or using a purposive sampling method with the sampling criteria being hydroponic vegetable farmers. Data analysis techniques use cost, revenue and income analysis. Based on the results and discussion, it is concluded that the hydroponic vegetable agribusiness system in Sambas Regency consists of an upstream subsystem including production facilities and infrastructure such as preparing planting media, seeds, nutrients/fertilizer, water, equipment and labor. The hydroponic vegetable farming system starts from preparing the land to harvesting and earns an average income of IDR Rp 1,122,890. The post-harvest subsystem includes cleaning, sorting and marketing activities. The marketing subsystem is carried out directly and indirectly. The subsystem or supporting institution that helps in hydroponic vegetable farming is the information system.